Intrusion notification via SMS / Aziz Kasmir Mat Yunos - Mat Yunos, Aziz Kasmir (Faculty of Information Technology and Quantitative Science, 2006)
This project is aimed to have an NIDS (Snort) intrusion notification via SMS in the real time. In order to achieve the project goals, the logdog Perl script have to be added new configuration to support snort log parsing and send SMS to Gnokii SMS gateway. Snort rule also have to be reconfigure to minimize SMS sent when intrusion detected. Beside that Bluetooth configuration also need to be tweak so it supports Nokia 6280 mobile phone that work as GSM modem. The outcome of this project is a reliable NDIS Intrusion Notification via SMS that support real time intrusion detection alert notification.